A leitura como prática emancipatória nos romances austenianos: Mansfield Park (1814) e Northanger Abbey (1818) - Caporale, Camila Cano (Universidade Federal de São Carlos, 2023)
Jane Austen is the author of novels in which have great prestige in the literary scene, mainly because she highlights aspects of English society to which she was linked. Among the most studied aspects, we mention the issue of women and marriage and irony. We, however, see and intend to investigate more deeply in this doctoral thesis a third major source for the recognition of social issues which were present in his time, namely, the issue of reading as a relevant and emancipatory practice for his reading characters. There will be two novels, with which we will seek to develop our work proposal: Mansfield Park (1814), Northanger Abbey, with the publication of the later dated in (1818). Both novels were the last of his career, considered fundamental in terms of analysis and questions about reading as a source of emancipation for the protagonist readers in the novels highlighted above. In both texts, literary analysis will be subordinated to the so-called three-horizon reading proposed by Fredric Jameson, (1992), considering political and social aspects present within the texts and the themes mentioned above.
Reading as an emancipatory practice in austenian novels: Mansfield Park (1814) And Northanger Abbey (1818)
Keywords: Jane Austen; Literatura inglesa oitocentista; Leitores; Leitura; Emancipação; Mansfield Park; A Abadia de Northanger; Nineteenth-century english literature; Readers; Reading; Emancipation; Jane Austen; Mansfield Park; Northanger Abbey; LINGUISTICA, LETRAS E ARTES::LETRAS::LITERATURAS ESTRANGEIRAS MODERNAS